IMPACT OF STREET-HAWKING ON THE EDUCATION OF YOUNG GIRLS IN THE SOGAKOFE COMMUNITY, VOLTA REGION, GHANA (Proceedings of the International Conference on Social Sciences, 2023)
In developing countries, street hawking, or the direct sale of retail goods on congested city streets, is a widespread occurrence. The majority of African cities, towns, and district capitals are particularly hard hit. The goal of this study was to investigate how street hawking affects the education of young female hawkers in Ghana's Volta region. The study used a descriptive research approach and selective sampling to pick 60 respondents from a population of 17,335 adolescent schoolgirls hawking along the main roadway. Findings revealed that schoolgirls in the age groups 16-20 and 21-25 dominated the street hawking trade. The predisposing factors identified include the need to pay their school fees, provide for their basic needs, assist their parent in providing for the home, and parental irresponsibility. In addition, the study found that many female street hawkers are not able to attend school regularly as a result of their hawking activities on the street, which affects school attendance and culminates in poor academic performance. Most of them become school dropouts. The study recommended that the government continue to educate parents about the negative effects of involving their children in street hawking and the importance of education, as well as that the government creates more employment opportunities so that citizens can provide for their families needs, such as paying for their children's education. Furthermore, affirmative action should be taken against the practice in order to protect the future of these young girls.
Keywords: street-hawking, young-females, education, school-performance